Blink and masseter inhibitory reflexes in Parkinson's disease - Stamenović Jelena; Đurić Stojanka; Đurić Vanja (Vojnosanitetski Pregled)
Background/Aim. Idiopathic Parkinson's disease (PD) is a chronic, progressive, neurodegenerative disorder with prevalence from 60 to 187 per 100 000 persons in general population. The aim of the study was to determine the abnormalities of the blink reflex (BR) and the masseter inhibitory reflex (MIR) in parkinsonian patients, as indices of the functional status of brainstem neuronal network, and abnormality level dependence on disease progression. Methods. The investigation was conducted at the Clinic of Neurology, Clinical Center Niš, comprising a group of 60 subjects of both sexes, suffering from idiopathic Parkinson's disease in I-IV stages, according to the Hoehn and Yahr scale. The control group included 30 healthy subjects of both sexes and corresponding age. Testing of the patients was performed during the 'on' phase by registering MIR and BR. Results. Latency of polysynaptic R2 and R2' blink reflex responses and latency of polysynaptic S2 response, as well as a silent period of MIR, are linearly shortened in the subjects with PD, and more expressed in the subsequent stages of the disease compared to the control group. Conclusion. There is a positive correlation between the applied neurophysiological tests results and clinical stage of PD.